Re-Layout Design of the Kalus 1.6 Warehouse Using the Class-Based Storage Method at PT XYZ - Muhammad Rafii Fadillah; Fakhrina Fahma (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2023)
PT XYZ is a company engaged in the electricity sector, where the main tasks are to produce, distribute, and provide electricity to the public. PT XYZ has Distribution Parent Units, such as the Greater Jakarta Distribution Parent Unit, which is responsible for distributing electricity in Jakarta and electrical equipment such as Miniature Circuit Breakers (MCB), Molded Case Circuit Breakers (MCCB), Kilowatt Hour (kWh) Meters, and others. Problems that exist in the Kalus Warehouse 1.6 of PT XYZ include the placement of goods that are less organized and the First In First Out (FIFO) system has not been running properly. This research aims to see the application of the fishbone diagram and class-based storage method in the Kalus Warehouse 1.6 of PT XYZ which previously still used a randomized storage system, namely the placement of goods randomly in any available space. The method used is to determine the cause of the problems that have been mentioned, design a layout with a minimum total displacement distance and optimize the allocation of types of goods. Based on the ranking of T/S calculation results, 2 proposed layouts were generated. Then, the two layouts are compared to find the most suitable warehouse layout which is the optimal condition with a decrease in rectlinear travel distance which is greater than the existing travel distance. to be applied to the Kalus Warehouse 1.6 of PT XYZ.